1999
DOI: 10.1046/j.1365-294x.1999.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtle population structuring within a highly vagile marine invertebrate, the veined squid Loligo forbesi, demonstrated with microsatellite DNA markers

Abstract: Microsatellite DNA markers were applied for the first time in a population genetic study of a cephalopod and compared with previous estimates of genetic differentiation obtained using allozyme and mitochondrial DNA (mtDNA) markers. Levels of genetic variation detected with microsatellites were much higher than found with previous markers (mean number of alleles per locus=10.6, mean expected heterozygosity (HE)=0.79; allozyme HE=0.08; mtDNA restriction fragment length polymorphism (RFLP) HE=0.16). In agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
123
2
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(151 citation statements)
references
References 54 publications
18
123
2
5
Order By: Relevance
“…Similar results have been found in several other studies comparing mtDNA and microsatellite data (e.g., Shaw et al 1999;Krafsur 2002;Diaz-Almela et al 2004;Lemaire et al 2005;Peijnenburg et al 2006). As the effective mitochondrial population size (N e ) is expected to be four times smaller than the nuclear N e , assuming both 1:1 sex ratios and diploidy (Birky et al 1983), there is a higher potential for genetic drift in mtDNA, which leads to a higher θ.…”
Section: Spatial Structuresupporting
confidence: 86%
See 2 more Smart Citations
“…Similar results have been found in several other studies comparing mtDNA and microsatellite data (e.g., Shaw et al 1999;Krafsur 2002;Diaz-Almela et al 2004;Lemaire et al 2005;Peijnenburg et al 2006). As the effective mitochondrial population size (N e ) is expected to be four times smaller than the nuclear N e , assuming both 1:1 sex ratios and diploidy (Birky et al 1983), there is a higher potential for genetic drift in mtDNA, which leads to a higher θ.…”
Section: Spatial Structuresupporting
confidence: 86%
“…As the effective mitochondrial population size (N e ) is expected to be four times smaller than the nuclear N e , assuming both 1:1 sex ratios and diploidy (Birky et al 1983), there is a higher potential for genetic drift in mtDNA, which leads to a higher θ. Ratios significantly higher than fourfold can be caused by sex bias in migration, reproduction or population size or by a difference in the mutation rate of the two markers (Turan et al 1998;Shaw et al 1999). The average θ C / θ N ratio in A. aranciacus is slightly higher than fourfold, for which the mentioned possibilities of sex bias or differences in mutation rates, combined or separately, could be partly responsible.…”
Section: Spatial Structurementioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, the genetic structure of numerous organisms has been assessed using several kinds of estimators, resulting in the discovery of disparate levels of genetic differentiation for different markers (Pogson et al, 1995;Lemaire et al, 2000;but see, Allendrof and Seeb, 2000). Although allozymes are still widely used, microsatellites have gained in importance due to their high levels of polymorphism, which facilitates the discovery of subtle differentiation (Ruzzante et al, 1998;Shaw et al, 1999). In addition, they are useful tools for the inference of historical dispersal and gene flow events, due to molecular insights into the nature of alleles and their mutation models (Balloux and Lugon-Moulin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite markers have shown considerable utility for genetic studies of population structure, particularly in organisms exhibiting low variability detectable by other methods (Hughes and Queller, 1993;Estoup et al, 1998). Several recent studies of widespread and abundant marine species (eg, squid, Shaw et al, 1999a;and herring, Shaw et al, 1999b) have indicated the greater capacity of microsatellite vs allozyme markers to detect fine population structure in such species. Microsatellites are also presumed to be neutral markers whereas allozymes have been suggested to be subject to selective forces, a potentially complicating factor when clinal frequency changes are found.…”
Section: Introductionmentioning
confidence: 99%